Development of a low cost alternative method for lipid extraction and quantification in food (Research, Society and Development, 2020)
Currently, the search for a healthy diet is more relevant in society. In this context, one of the great villains has been lipids therefore its quantification in the food industry is extremely important. This article proposes the analytical simplification of a method to extract and quantify lipids in food. Such simplification, the alternative extractor (AE), is based on the characteristics of the Soxhlet extractor, which allowed, quantitatively, to determine the levels of lipids in food using easily obtainable and low-cost materials and reagents. Therefore, a comparison was made between the extraction efficiency of the AE and the Soxhlet extractor, a standard procedure in food industry. The levels of lipids extracted and quantified for the selected food presented similar values for the two methods tested. Consequently, the AE is applicable as a substitute for the official method and can also be a practical low-cost tool in the teaching of Chemistry for simple experiments in the field of biochemistry.